An Investigation of the Impacts of Strategic Intelligence on Improving Organizational Innovation - Shahraki, Armita Maleki; Shahraki, Armita Maleki; ANSARI, Manouchehr; Keivani , Shirvan (International Journal of Psychosocial Rehabilitation, 2020)
Today, strategic intelligence can be defined as "what an organization should learn from its business environment in order to gain an understanding of its current processes, predict and manage future changes, and adopt appropriate strategies to create value for the customer and develop profitability in current and new markets." Strategic intelligence, as a determining factor in successful decision making, requires describing threats, risks and opportunities in a useful way, so that the organization’s programs and policies can be developed. On the other hand, teamwork and human resource participation are considered to be key or basic activities. Team-based organizations are able to make good use of human resources in a desired way and provide a good platform for competition in the market. The main objective of this study was to investigate the effect of strategic intelligence of managers on organizational innovation in Sina Insurance Company, Karaj. The research was of applied type and was performed via a correlation method. The statistical population of this research consisted of 152 employees at Sina Insurance Company in Karaj city, as 111 people were selected as a sample using Morgan Table. The standard Strategic Intelligence and Organizational Innovation Inventories were used to collect information, the validity of which was confirmed by professors and experts, with their reliability being 0.745 and 0.802, respectively using Cronbach’s alpha test. Statistical tests of correlation coefficients and linear regression were used to analyze and test research hypotheses. For this purpose, SPSS statistical software was used. The results from testing hypotheses demonstrated that strategic intelligence and its components had a significant effect on organizational innovation at Sina Insurance Company in Karaj. According to the results, suggestions were made for the statistical community and managers of the organization.